The Scope of Usage-Based Theory - Ibbotson, Paul (Frontiers in Psychology, 2013)
Usage-based approaches typically draw on a relatively small set of cognitive processes, such as categorization, analogy and chunking to explain language structure and function. The goal of this paper is to first review the extent to which the ‘cognitive commitment’ of usage-based theory has had success in explaining empirical findings across domains, including language acquisition, processing and typology. We then look at the overall strengths and weaknesses of usage-based theory and highlight where there are significant debates. Finally, we draw special attention to a set of culturally generated structural patterns that seem to lie beyond the explanation of core usage-based cognitive processes. In this context we draw a distinction between cognition permitting language structure versus cognition entailing language structure. As well as addressing the need for greater clarity on the mechanisms of generalizations and the fundamental units of grammar, we suggest that integrating culturally generated structures within existing cognitive models of use will generate tighter predictions about how language works.